Evaluation of chronic gastritis in patients with Helicobacter pylori associated gastritis, gastroduodenitis and duodenal ulcer disease - , Nevin BAĞATUR, Yeşim ERALP, Aykut ÇELİK, Ahmet DOBRUCALI, Kadir BAL, Murat TUNCER, Suha GÖKSEL, Hülya UZUNİSMAİL, Ergun OKTAY (Turkish Journal of Gastroenterology 1, 2019)
-